Meningkatkan Perkembangan Berpikir Anak Dalam Mengenal Bentuk Geometri Melalui Media Bermain Balok - Awalia Masruroh (Journal of Educational Research, 2022)
This study aims to find out that playing activities through playing blocks can improve children's cognitive development in recognizing geometric shapes. The results of research on children's cognitive development actions in recognizing geometric shapes through playing blocks in the pre-cycle media obtained 30.7% of children while in the first cycle it increased to 55.7%, in the second cycle increased by 80.54% in sorting the shape of the blocks and determining geometric shapes, in making geometric shapes in the pre-cycle, 45.8% of children in the first cycle rose to 60.25%, in the second cycle increased to 80.54% in making geometric shapes, in making geometric drawings in the pre-cycle obtained 34.0% children while the first cycle rose to 60.25%, while in the second cycle it increased to 78.35% in making geometric drawings , in building blocks in the pre-cycle it was obtained 55.7% of children while in the first cycle it increased to 65.53%, while in the second cycle it increased to 83.64% in the first cycle. building blocks. Penelitian ini bertujuan untuk mengetahui kegiatan bermain melalui media bermain balok dapat meningkatkan perkembangan kognitif anak dalam mengenal bentuk geometri.Hasil penelitian pada tindakan perkembangan kognitif anak dalam mengenal bentuk geometri melalui media bermain balok pada pra siklus diperoleh 30,7% anak sedangkan pada siklus I naik menjadi 55,7%,pada siklus II lebih meningkat 80,54% dalam mengurutkan betuk balok dan menentukan bentuk geometri, dalam membuat bentuk geometri pada pra siklus diperoleh 45,8% anak pada siklus I naik menjadi 60,25%, pada siklus II lebih meningkat menjadi 80,54% dalam membuat bentuk geometri, dalam membuat gambar geometri pada pra siklus diperoleh 34,0% anak sedangkan siklus I naik menjadi 60,25% , sedangkan pada siklus II lebih meningkat menjadi 78,35% dalam membuat gambar geometri, dalam membangun balok pada pra siklus diperoleh 55,7% anak sedangkan pada siklus I naik menjadi 65,53%, sedangkan pada siklus II lebih meningkat menjadi 83,64% dalam membangun balok.